The insight of domestic violence from the perspective of female victims in Ebiraland, Nigeria - Abdullahi, Umar (2018)
Domestic violence has been recognised as a global social problem and serious human rights violation. Literature has indicated harmful effects of violence on women, children, and the society in general. The problem of domestic violence in Ebiraland is at an alarming rate while the absence of significant studies of its factors and effects has been exhaustive. This study explores the perceptions of the Muslim women about domestic violence and examines the factors associated with it in Ebiraland. The views of Muslim women and suggestions are crucial in understanding the effects of domestic violence on women and children, and the nature of mechanisms needed in preventing the violence. This is a qualitative research. The data were obtained through in-depth semi structured interviews. Twenty informants were purposively selected from Adavi, Ajaokuta, Okehi and Okene Local Government Areas of Kogi State, Nigeria. Thematic content analysis approach was applied in this study where themes that emerged were analysed using NVivo software. The findings show that poverty, polygamy, infertility and change in religion are the main contributors to domestic violence in Ebiraland. The study also established that the elevated level of criminal in Ebiraland is significantly associated with domestic violence in matrimonial relationships. It was further revealed that women had a perception that domestic violence affect their physical, mental and reproductive life. The women also felt that socio-cultural norms gave rise to domestic violence in Ebiraland. This study contributed significantly to the perspectives on factors and effects of domestic violence against women and children. It is suggested that preventive interventions such as legislation, employment and women empowerment are essential in breaking the cycle of violence. Muslim leaders’ role of preaching and counselling the couples should be improved to ensure women’s safety.